Microbiome immune system interactions in selected neurological disorder - P. Omosigho; G. Sulaiman; O. Okesanya (Microbiota in Health and Disease)
Neurological disorders, such as Parkinson’s disease (PD), Alzheimer’s disease (AD), autism spectrum disorder (ASD), and multiple sclerosis (MS), have long been thought to affect only the central nervous system. However, recent research sheds light on their complexities, revealing complicated linkages beyond the central nervous system. Gastrointestinal symptoms, gut microbiota dysbiosis, and the gut-brain axis all play critical roles in the development and progression of these illnesses. The interaction between the gut microbiota and neurological function highlights the importance of the gut-brain axis in a variety of illnesses. Furthermore, dysbiosis in the gut microbiome has been linked to the pathophysiology of PD, AD, MS, and ASD. Changes in gut microbiota composition and neuroinflammation mediated by the NLRP3 inflammasome have been observed in AD, suggesting a connection between microbiological variables and the course of the illness. Similarly, studies have found that MS patients have different microbial profiles than healthy people, indicating that the microbiome plays a role in illness development. Anxiety, depression, and stroke have all been linked to changes in the gut microbiota, emphasizing the broader implications of microbiome-immune system interactions in neurological health. Researchers should collaborate, conduct longitudinal studies tracking gut microbiota changes in at-risk populations, use precision medicine approaches tailored to individual microbiota composition, and promote gut health from birth.